Common Ownership of Competing Firms: Evidence from Australia. Issue 318 (26th May 2021) - Leigh, Andrew; Triggs, Adam
Abstract : This paper provides the first estimates of the extent of common ownership of competing firms in Australia. Combining data on market shares and substantial shareholdings, we calculate the impact of common ownership on effective market concentration. Among firms where we can identify at least one owner, 31 per cent share a substantial owner with a rival company. Analysing 443 industries, we identify 49 that exhibit common ownership, including commercial banking, explosives manufacturing, fuel retailing, insurance and iron ore mining. Across the Australian economy, common ownership increases effective market concentration by 21 per cent. Our estimates imply that if listed firms seek to maximise the value of their investors' portfolios, then they place the same value on 3.70 of their competitors' profits as on 1 of their own profits. We discuss the limitations of the available data, and the potential implications of common ownership for competition in Australia.